Media dan Peace Building: Media Literacy for Sekolah Wijaya Kusuma Students - Adeline, Clarissa; Naha, Rambu; Yang, Angela Adriyanti (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
Abstract Globalization changes the nature of media and information dissemination, where media plays an important part in enhancing peace. But on the other hand, media is not only a tool to promote harmony but conflict as well. However, peacebuilding depends largely on media literacy. Media literacy offers people potentialities to promote peace, especially at young ages. Therefore, this program aims to help students improve their media literacy competence, specifically regarding how to use media wisely. This program also collaborates with Jawara Internet Sehat to promote the internet for positive use to 100 Wijaya Kusuma School students. The implementations of this program are divided into 3 stages, preparation, delivery, and evaluation. The preparation stage focused on analyzing the problems faced by Sekolah Wijaya Kusuma to help us build suitable training modules. Then in the delivery stage, we conduct training through seminars and workshops that focus on using media wisely and avoiding hoaxes. And lastly, we evaluate the feedback given by the students and the result shows that this program helps the student to improve their media literacy and promote peacebuilding through media.